Molecular Docking Studies of Compounds from Brucea javanica (L.) Merr. Towards The Discovery of Potential H5N1 Neuraminidase Inhibitors - Rina Fajri Nuwarda; Zelika Mega Ramadhania; Imam Adi Wicaksono; Muhammad Yusuf; Ade Rizqi Ridwan Firdaus; Muchtaridi Muchtaridi (Indonesian Journal of Pharmaceutical Science and Technology, 2020)
The occurrences of a highly pathogenic avian influenza virus (HPAI) type A H5N1 has caused infections in millions of poultry as well as hundreds of human cases and even mortalities. Indonesia has become one of the world’s highest casualty rates of H5N1 human infections, with the number of deaths was 167 from a total of 199 cases. The development of viral resistance towards the available anti-influenza drugs neuraminidase (NA) inhibitors required the discovery of new inhibitors. In the recent advance of drug discovery, natural products have been considered as one of the essential sources of medicinal agents, and Brucea javanica has been found to possess antiviral activity against H5N1 NA. Thus, this research aimed to investigate the in silico activities of compounds from B. javanica using molecular docking methods against H5N1 NA. In this study, docking-based virtual screening of compounds from B. javanica to quickly select in silico hits to be potential NA inhibitors was performed. Subsequently, the intermolecular interactions of the inhibitor compounds with the H5N1 NA were analysed to examine the most preferred interactions. The results showed that brucein G and bruceoside C were found having the lowest binding energy and most preferred interactions with H5N1 NA and therefore, can be proposed for further study as potential NA inhibitors.Keyword: antiviral, Brucea javanica, H5N1, molecular docking, neuraminidase